The Importance of Aphasia Communication Groups - Charalambous, Marina; Kambanaros, Maria (My University, 2021)
Chronic aphasia is linked to poor functional recovery, depression, and social isolation. In the exploration of the above factors the role of aphasia communication groups has evolved. Aphasia communication groups for stroke survivors with chronic aphasia and their communication buddies are gaining clinical importance. Communication buddies can be family members, friends, carers, health professionals and speech and language therapy students who serve as communication facilitators for each group member. Group members share experiences on stroke and aphasia by using technology/tablets and the total communication approach. The benefits or outcomes of group involvement are measured by assessment of functional communication, individual self-ratings of the impact of aphasia on communication and quality of life after stroke. The use of the communication buddy system, total communication approach and systematic evaluations enables therapists to measure the effectiveness and efficacy of communication groups in terms of functional communication, social inclusion and quality of life.
Keywords: aphasia communication groups; communication buddies; quality of life